Loci de caracteres cuantitativos para rasgos reproductivos en bovinos lecheros locales - Raschia, Maria Agustina; Maizon, Daniel Omar; Amadio, Ariel; Poli, Mario Andres (Sociedad Argentina de Genética, 2022)
Póster